Analysis the Poverty of Fisherman Coastal Society area in the Waplau Subdistrict of Buru district - Fesanrey, Wilda; Umasugi, Samsia (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Poverty experienced by poor families in fishing settlements in Waplau District occurs because of factors that arise from within themselves and local environmental factors. Poverty arises from oneself because people's lifestyles are extravagant. Meanwhile, environmental factors mean that fishermen's income is not fixed based on weather conditions suitable for fishing. The purpose of this research to steeped in the kind poverty of fisherman, analyze revenue and expenditure fishermen, analyze the factors that affect poverty of fisherman, and to find alternative solutions to reduce poverty of fishermen in the Waplau subdistrict. Technique for sampling done â€œproposive samplingâ€ on respondents in research areas, and only those involved in the issue. From the result of this study indicate that the respondents fishermen poverty in Waplau subdistrict is absolute poverty. The average income earned by Rp. -110.722. respondents fishermen. Factors affecting fishing poverty in Waplau subdistrict that is factor income, expenditure and education.